Metal organic framework composite, nano-Fe3O4@Fe-(benzene-1,3,5-tricarboxylic acid), for solid phase extraction of blood lipid regulators from water - Peña-Méndez, E M; Mawale, R M; Conde-González, J E; Socas-Rodríguez, B; Havel, J; Ruiz-Pérez, C (Talanta, 2020)
The magnetic metal-organic framework Fe3O4@(Fe-(benzene-1,3,5-tricarboxylic acid) (MMOF) was prepared, characterized and studied as a magnetic sorbent for the dispersive solid-phase extraction (DSPE) of several widely used blood lipid regulators (i.e., bezafibrate, clofibric acid, clofibrate, gemfibrozil and fenofibrate) from water samples. Characterization of the synthesized Fe3O4@Fe-BTC magnetic nanomaterial was performed by Fourier transform infrared spectroscopy, powder X-ray diffractometry, thermogravimetric analysis, scanning electron microscopy and transmission electron microscopy. The magnetic nanocomposite was found to be chemically stable and to possess a large surface area (803.62 m2/g) and pore volume (0.59 cm³/g). The concentrations of fibrates in different water samples were determined using HPLC-UV-Vis and confirmed by UPLC-MS/MS. Parameters affecting the extraction efficiency of magnetic-DSPE were studied and optimized. The maxima absorption capacities (Qmax) were determined to be (in mg/g) 197.0 for bezafibrate, 620.3 for clofibric acid, 537.6 for clofibrate, 288.7 gemfibrozil and 223.2 for fenofibrate. Validations of the optimized magnetic DSPE method for analyses at two fibrate concentrations in spiked water samples produced relative recovery values ≤ 70% for clofibrate and within the range of 80-100% for bezafibrate, clofibric acid, gemfibrozil and fenofibrate. LODs ranging from 4 μg/L for fenofibrate to 99 μg/L for gemfibrozil were obtained. The validated methodology produced recovery values ranging from 70 to 112% (relative standard deviations < 7%).
Keywords: železo; Solid Phase Extraction; Water Pollutants, Chemical; extrakce na pevné fázi; magnetické nanočástice; kyseliny trikarboxylové; Tricarboxylic Acids; porézní koordinační polymery; Water; Iron; Benzene; Lipid Regulating Agents; látky regulující metabolismus lipidů; Magnetite Nanoparticles; benzen; voda; chemické látky znečišťující vodu; Metal-Organic Frameworks